2021
DOI: 10.1158/1535-7163.mct-20-0167
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib Unlocks Efficient In Vivo Targeted Delivery of Neutrophil-Loaded Nanoparticles into Murine Prostate Tumors

Abstract: A major barrier to the successful application of nanotechnology for cancer treatment is the suboptimal delivery of therapeutic payloads to metastatic tumor deposits. We previously discovered that cabozantinib, a tyrosine kinase inhibitor, triggers neutrophil-mediated anticancer innate immunity, resulting in tumor regression in an aggressive PTEN/p53-deficient genetically engineered murine model of advanced prostate cancer. Here, we specifically investigated the potential of cabozantinib-induced neutrophil acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…(e) Concentration of DiO-OPNP was determined by the fluorescence method, and percentage of OPNP uptake was calculated according to the dose of OPNPs administered ( n = 3). Reproduced with permission from ref . Copyright 2021 American Association for Cancer Research.…”
Section: Opnps-mediated Pdt For Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…(e) Concentration of DiO-OPNP was determined by the fluorescence method, and percentage of OPNP uptake was calculated according to the dose of OPNPs administered ( n = 3). Reproduced with permission from ref . Copyright 2021 American Association for Cancer Research.…”
Section: Opnps-mediated Pdt For Prostate Cancermentioning
confidence: 99%
“…91,92 Building on these findings, Chaudagar and colleagues conducted a study to enhance the targeted delivery of BSA-coated organic polymeric nanoparticles (BSA-OPNPs) to the prostate tumor region by inducing neutrophil activation and aggregation using cabozantinib. 93 To ensure that the internalization of OPNPs by neutrophils does not adversely affect their activation, researchers conducted an experiment in which neutrophils were incubated with varying amounts of DiR-loaded BSA-OPNP (10, 100, and 1000 μg) in 1.4 mL of conditioned medium. The results demonstrated that the binding of BSA-OPNPs did not alter neutrophil activation or function across a range of doses.…”
Section: Targeting Prostate Tumor Cells Based On Neutrophilsmentioning
confidence: 99%
“…Therefore, a study also showed that bovine serum albumin (BSA)-coated polymeric nanoparticles (BSA-NPs) can significantly enhance cabozantinibinduced, neutrophil-mediated targeted intratumoral drug delivery. 214 Because inflammatory factors released after tumor resection guide the movement of the neutrophils into the inflamed brain, neutrophils carrying cationic liposomes that contain PTX (PTX-CL) have been shown to penetrate the brain and suppress the recurrence of glioma in mice whose tumors have been resected surgically. 215 The receptors for monomer of poly(sialic acid) (PSA) are expressed on peripheral blood neutrophils, and PSA-modified liposomes provide greater uptake to neutrophils than plain liposomes and PEGmodified liposomes; therefore, pro-PSA-octadecylamine conjugate anchored on the surface of liposomal pixantrone provided an increased accumulation of liposomes in peripheral blood neutrophils and enhance neutrophil-mediated pixantrone delivery for eradication of tumors.…”
Section: Nanoparticles For Modulating Neutrophilsmentioning
confidence: 99%
“…BSA-coated, dye-loaded nanoparticles were injected into prostate-specific PTEN/p53-deficient mice pretreated with cabozantinib. Their findings indicate that coating nanoparticles with BSA can improve cabozantinibinduced, neutrophil-mediated targeted intratumoral drug delivery while reducing off-target effects (55). The deliveries of apatinib and cediranib using polymeric nanoparticles were tested for osteosarcoma and glioblastoma, respectively.…”
Section: Nanotechnology As the Potential Delivery Systemmentioning
confidence: 99%